Sudden Infant Death Due to Misdiagnosis of Hypoplastic Left Heart Syndrome: A Case Report - Sadeghi, Sajjad (Jour Med Resh and Health Sci, 2024)
Heart abnormalities are the most prevalent congenital defects, with Hypoplastic Left Heart Syndrome (HLHS) being a critical type marked by the left heart’s underdevelopment. Immediate diagnosis and intervention are crucial to avert dire consequences like sudden infant death. The report described the sudden death of a 4.5-month-old female infant, who showed symptoms like cyanosis, dyspnea, and distress while crying and breastfeeding. On the day of the incident, the infant experienced a seizure after crying for 10 minutes. She passed away in the Emergency Department due to resistant bradycardia. The case highlights the devastating effects of misdiagnosis and the difficulties in detecting complex HLHS, underlining the urgency for increased vigilance, and the use of diagnostic techniques.